PENGGUNAAN GEOGEBRA 6.0.462.0 PADA PERMASALAHAN PROGRAM LINIER BAGI GURU MATEMATIKA SMA SE-ACEH TAMIANG - Ulya Nabila; Nurviana Nurviana; Amelia Amelia; Fitra Muliani (LPPM dan PM Universitas Samudra, 2020)
Teachers as educators are required to be able to develop and apply various learning methods, through media, tools and resources in learning. The use of software, such as GeoGebra 6.0.462.0, is an attempt to make the learning process more varied and interesting. The purpose of this activity is to provide training to high school teachers to solve problems related to linear programs. A direct approach method, namely through lectures and practices are used in this activity. The lecture method is carried out by providing information to the teacher about the advantages and benefits of GeoGebra 6.0.462.0 as one of the powerful mathematical software in helping to solve problems related to linear programs. While the practice method is carried out by providing GeoGebra 6.0.462.0 software training. The results of this activity were that the teachers were able to use GeoGebra 6.0.462.0 to solve linear program problems.